Die Einheit der Schrift und die Vielfalt des Kanons / The Unity of Scripture and the Diversity of the Canon - Barton, John; Wolter, Michael (Beihefte zur Zeitschrift für die neutestamentliche Wissenschaft und die Kunde der älteren Kirche, 2003)
Biographical note: The Revd. Professor John Barton is Oriel and Laing Professor of the Interpretation of Holy Scripture at Oriel College Oxford. Dr. Michael Wolter is Professor of New Testament Studies at the Rhenish Friedrich-Wilhelms University of Bonn.